The HIV-1 reverse transcriptase polymorphism A98S improves the response to tenofovir disoproxil fumarate + emtricitabine-containing HAART both in vivo and in vitro. (December 2016) - Alteri, Claudia; Surdo, Matteo; Di Maio, Velia Chiara; Di Santo, Fabiola; Costa, Giosuè; Parrotta, Lucia; Romeo, Isabella; Gori, Caterina; Santoro, Maria Mercedes; Fedele, Valentina; Carta, Stefania; Continenza, Fabio; et al.
Highlights: Role of baseline HIV-1 RT polymorphisms on response to TDF + FTC-based HAART was defined. A98S mutation increased virological success at Week 24 of treatment. In vitro and structural data support that A98S increased susceptibility to TDF and FTC. These findings may help clinicians in the selection of the optimal NRTI backbone. Abstract: The impact of baseline HIV-1 reverse transcriptase (RT) polymorphisms on response to first-line modern HAART containing tenofovir disoproxil fumarate (TDF) and emtricitabine (FTC) was evaluated. The impact of each RT polymorphism on virological success (VS) was evaluated in 604 HIV-1 subtype B-infected patients starting TDF + FTC-containing HAART. TDF and FTC antiviral activity was also tested in PBMCs infected by mutagenised HIV. Structural analysis based on docking simulations was performed. A98S was the only mutation significantly correlated with an increased proportion of patients achieving VS at 24 weeks (94.0% vs. 84.3%; P  = 0.03). Multivariate regression and Cox model analyses confirmed this result. At concentrations close to the minimal concentration achieved in patient plasma, TDF and FTC exhibited higher potency in the presence of A98S-mutated virus compared with wild-type (IC90, TDF, 8.6 ± 1.1 vs. 19.3 ± 3.5 nM; and IC90, FTC, 12.4 ± 7.7 vs. 16.8 ± 9.8 nM, respectively). The efficacy of FTC, abrogated by M184V, was partially restored by A98S (IC90, FTC, 5169 ± 5931 nM for A98S + M184V vs. 18 477 ± 12 478 nM for M184 V alone). Docking analysis showed the higher potency of TDF and FTC in the presence of A98S-mutated virus was mainly due to higher binding affinity between drugs and mutated RT compared with wild-type. In the presence of FTC, A98S also partially restored the RT binding affinity impaired by M184V alone. A98S polymorphism improves virological response to TDF + FTC-containing HAART. This may help clinicians in the choice of the optimal NRTI backbone aimed at achieving maximal virological inhibition.